SIFAT ANATOMI, SIFAT FISIS DAN MEKANIS PADA KAYU KEMENYAN TOBA (Styrax sumatrana) DAN KEMENYAN BULU (Styrax paralleloneurus) - Gunawan Pasaribu; Jasni; Ratih Damayanti; Santiyo Wibowo (Jurnal Penelitian Hasil Hutan, 2013)
Gum benzoin (Styrax sp.) is a tree producing resins that have bigh economic value originated from North Sumatra Province. The unproductive trees (less resin production) are harvested by the community for firewood. This paper presents characteristics difference of two types of Kemenyan toba (Styrax sumatrana) and Kemenyan bulu (Styrax paralleloncurus) in anatomical, phisical and mechanical properties in order to use properly. The results showed that kemenyan toba wood and kemenyan bulu are unique anatomical properties. The quality of fiber as a raw material for pulp is categorized into first quality. Based on their spesific gravity, the wood were clasified as medium beavy, with stabile shrinkage. Both wood are suitable for non structural construction, furniture and bandicraft.